Sustainable agriculture, aquaculture and phytoremediation through freshwater macrophytes: a comprehensive review of mineral uptake, soil health, and water quality dynamics - Lone Rafiya Majeed; Deeplata Sharma; Kuldeep Singh Rautela; Mohit Kumar (Discover Water)
Abstract Freshwater macrophytes thrive in tropical and subtropical climates, providing valuable feed ingredients for a variety of aquatic and terrestrial animals while also influencing hydrology, sediment dynamics, and biogeochemical cycles. The purpose of this review is to assess the viability of freshwater macrophytes as a sustainable source of minerals for agriculture. To provide a comprehensive understanding of the topic, over 120 studies published across diverse geographic regions with diverse climates, precipitations and topography, were reviewed, with a focus on different species and methodologies. Key findings show that anthropogenic introductions of exotic freshwater macrophytes pose significant ecological risks due to their rapid growth in new habitats, which can disrupt local ecosystems. However, the biomass derived from these plants has a wide range of applications, including animal feed, biofuel, and ceramics, as well as biological markers and environmental remediators. Furthermore, fresh tissues, dried matter, manure, ensilage, and biochar are examples of in-situ applications of freshwater macrophytes that have shown to have major benefits for agricultural practices. These applications promote healthy plant growth, raise crop yields, lessen the need for chemical fertilizers, and decrease crop disease rates. The review also covers these organisms’ ability to produce antibacterial compounds, remove heavy metals and other pollutants from soil and water, and enhance soil quality and biodiversity in general. The results collectively highlight the significance of freshwater macrophytes in fostering ecological balance and resource efficiency, as well as their potential to support environmentally friendly farming methods and environmental conservation. Graphical Abstract